2009
DOI: 10.1038/cdd.2009.142
|View full text |Cite|
|
Sign up to set email alerts
|

Ubiquitin B: an essential mediator of trichostatin A-induced tumor-selective killing in human cancer cells

Abstract: Although histone deacetylase inhibitors (HDACis) are emerging as a new class of anticancer agents, the mechanism of tumorselective killing by HDACi is not well understood. We used suppression of mortality by antisense rescue technique (SMART) to screen the key genes responsible for the tumor-selective killing by trichostatin A (TSA). Twenty-four genes were identified, the most significant of which was ubiquitin B (UbB). The expression of UbB was selectively upregulated by TSA in tumor cells, but not non-malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
3
16
0
2
Order By: Relevance
“…12 In this study, further analysis indicated that FAM210B was a novel mitochondria outer membrane protein and low expression of FAM210B obviously promoted malignant metastasis in vitro and in vivo. Depletion of FAM210B in ovarian cancer cells displayed elevated mitochondrial respiration and decreased glycolysis relative to control cells via the suppression of its downstream target, pyruvate dehydrogenase kinase 4 (PDK4).…”
mentioning
confidence: 63%
“…12 In this study, further analysis indicated that FAM210B was a novel mitochondria outer membrane protein and low expression of FAM210B obviously promoted malignant metastasis in vitro and in vivo. Depletion of FAM210B in ovarian cancer cells displayed elevated mitochondrial respiration and decreased glycolysis relative to control cells via the suppression of its downstream target, pyruvate dehydrogenase kinase 4 (PDK4).…”
mentioning
confidence: 63%
“…To investigate the potential of functional polyesters to be cancer specific, we delivered a pan-toxic siRNA targeting UBB (27,28) to lung cancer and normal cells derived from single patient to discover cancer cell-selective NPs that show more efficacious siUBB delivery to tumor cells over matched normal cells ( Fig. 2A and SI Appendix, Table S1).…”
Section: A Scalable Methods Enabled Synthesis Of Polyesters With Divermentioning
confidence: 99%
“…1A) in vitro and in vivo. We delivered siRNA targeting ubiquitin B (siUBB) (27,28), which causes cell death in all cell types to evaluate the delivery selectivity to HCC4017 tumor cells over HBEC30-KT normal cells. NPs were identified that showed selective cellular uptake to cancer cells over normal cells followed by reduced transport to lysosomes.…”
Section: Significancementioning
confidence: 99%
“…Quantitative PCR was done in an ABI Prism 7000 using the SYBR Green PCR Master Mix (Sigma) as our previous description (27) with the following set of primers: CD146, 5′-CAG TCC TCA TAC CAG AGC CAA CAG-3′ and 5′-GGA CCA GGA TGC ACA CAA TCA-3′; E-cadherin, 5′-GGA TTG CAA ATT CCT GCC ATT C-3′ and 5′-AAC GTT GTC CCG GGT GTC A-3′; β-catenin, 5′-AAC GTT GTC CCG GGT GTC A-3′ and 5′-GGC AAG ATT TCG AAT CAA TCC AAC-3; integrin β1, 5′-GCC TTA CAT TAG CAC AAC ACC-3′ and 5′-CAT CTC CAG CAA AGT GAA AC-3; ICAM-1, 5′-CCT GAT GGG CAG TCA ACA GCT A-3′ and 5′-ACA GCT GGC TCC CGT TTC A-3′; VCAM-1, 5′-CGT GAT CCT TGG AGC CTC AAA TA-3′ and 5′-GAC GGA GTC ACC AAT CTG AGC A-3′; selectin-E, 5′-CAC TCA AGG GCA GTG GAC ACA-3′ and 5′-CAG CTG GAC CCA TAA CGG AAA C-3′; 18S, 5′-AGT CCC TGC CCT TTG ACA CA-3′ and 5′-GAT CCG AGG GCC TCA CTA AAC-3′. 18s RNA was used as an internal control.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%